Constructing Industry-Ready Identities: A Narrative Study of TVET Students in Production Engineering Project-Based Learning Models - Eko Indrawan; Bulkia Rahim; Jasman Jasman; Rizki Hardian Sakti; Rizky Ema Wulansari; Siti Afiat Jalil (International Journal of Educational Narratives, 2026)
Background. The blistering working development of intelligent manufacturing technologies due to the Industry 4.0 level achievements has had a considerable impact on industrial practice, which generates an urgent demand among vocational graduates who can not only be highly qualified in their technical skills but also adapt to the new digital tools. Traditional methods of teaching Production Engineering and NC (Numerical Control) Programming also favor theory rather than practice leading to a disconnect between the theoretical content of classroom study and practical needs in the industry. Purpose. This research aims on creating and executing a Smart Manufacturing-Oriented Project-Based Learning (PBL) Model that will help to combine the real-world industrial problems with the latest technologies CNC simulation software and digital manufacturing instruments. Method. This study employs a Research and Developmet (R&D), with 68 students of vocational higher education who were taking Production Engineering and NC Programming courses as sample. Performance assessments, observational analysis, and feedback surveys were used to collect the data. Results. Findings indicate that the suggested model significantly enhanced the proficiency of students to learn and master NC programming, optimization of production workflow, and solve problems in the technology-saturated settings. There was also an improvement in collaboration, project management, and adaptation of smart manufacturing tools by students. The model ensures a closer alignment between student learning outcomes and industry performance requirement through smart technnology integration. To sum up, the Smart Manufacturing-Oriented PBL Model is an effective approach that helps to bridge the gap between the academic and the industrial community and develop industry-oriented skills and equip graduates with the requirements of digitalized manufacturing industries. Conclusion. This study provides a flexible and generalizable model of applying smart manufacturing concepts to the technical education in order to make graduates more employable in the dynamic industrial environment.